-NA- BAJAK LAUT DI ASIA TENGGARA ABAD 16 – 19: EVOLUSI DAN POLA-POLANYA - Budiawan, Budiawan (JURNAL ILMU BUDAYA, 2025)
Historically sea has been a theatre for action, in which one party exercised its power over the others. But, is the history of maritime piracy as old as the history of human activities in seas? What is maritime piracy itself? Who can be considered maritime pirates? This question emerges because the definition of maritime piracy itself is dynamic. It changes in line with the changing contexts of space and time. This article attempts to answer these questions by referring to the case of maritime piracy in Southeast Asia from sixteenth to nineteenth century. This article aims to show the dynamics of the meaning of maritime piracy, and how such a notion could turn to be a convention. It uses secondary sources since it has no pretension to contribute new data, but rather it aims at showing how a notion of maritime piracy could turn to be a regime of truth.